Artificial Intelligence In The Big Data Era And Digital Audit - Revita Chikita Meitasari; Angela Haga Audrey (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2023)
The technology industry has entered the 4.0 era, also known as the Artificial Intelligence (AI) era, which has greatly affected various aspects of human life, particularly with the advancement and growth of big data. The integration of AI in our daily lives, including accounting, has made work more efficient, but also brought both positive and negative impacts. The accounting industry is moving towards the digital audit era, which has transformed the perspective of auditors by digitizing their work and making it easier to access and analyze data. This study aims to investigate the impact of AI development on big data and digital audit, the implications of the gap between big data technology and AI and digital audit, as well as the improvement of auditor's work quality and efficiency due to AI and big data technology. The study utilized both quantitative and qualitative research methods, and concludes that the development of Artificial Intelligence has a significant impact on the work of auditors. However, the study acknowledges its limitations, such as the restricted sample size and time constraints which limited the data analysis to multiple linear regression analysis.